Syarat Perlu dan Cukup untuk Keterbatasan Potensial Riesz di Ruang Morrey Klasik - Utoyo, Mohammad Imam; Widodo, Basuki; Nusantara, Toto; Suhariningsih, Suhariningsih (Jurnal Natur Indonesia, 2012)
This script was aimed to determine the necessary conditions for boundedness of Riesz potential in the classical Morrey space. If these results are combined with previous research results will be obtained the necessary and sufficient condition for boundedness of Riesz potential. This necessary condition is obtained through the use of characteristic function as one member of the classical Morrey space.